Development of an electronic payment system using the Internet of things - Talib, Ahmed Abdulkarim; Salman, Aymen Dawood (IAES International Journal of Robotics and Automation (IJRA), 2022)
Smartphone has become more widely used than ever and become necessary to develop electronic payment systems using the internet of things (IoT) techniques with the smartphone. Payment solution is one of the most important issues in the IoT. It is the future to make life easier and better through the new relationships will be commercial, requiring payment for services and products. This paper develops a prototype of a payment system consisting of a network from several interconnecting devices such as radio frequency identification (RFID) reader, RFID card tag, equipped with microprocessors NodeMCU, and corresponding software represented by an interactive website for making process of purchase, a database (MySQL) for store data of payments. Focusing on the side of protecting the payment system, a security model for a simplistic payment system based on the IoT is represented by using biometric authentication in the sensor of smartphones like fingerprint authentication and face detection to make sure the identification of the user before making the payment process in the system.